The University of Iowa Guide to Campus Architecture, Second Edition - Scott, John Beldon, 1946- (Book collections on Project MUSE., 2016)
"In this guide to the University of Iowa's architecture, revised and updated to reflect the numerous changes following the 2008 flood, John Beldon Scott and Rodney P. Lehnertz discuss and illustrate an ensemble of buildings whose stylistic diversity reflects the breadth of Iowa's contributions to research, education, and creative activities. Current students and their parents, alumni, and professional and amateur architecture enthusiasts will appreciate this informative tour of the university's distinctive campus"--